2017
DOI: 10.1080/00934690.2017.1338513
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Best Practices for Photogrammetric Recording During Archaeological Fieldwork

Abstract: Archaeologists have recently embraced photogrammetry as a low-cost, efficient tool for recording archaeological artifacts, active excavation contexts, and architectural remains. However, no consensus has yet been reached about standard procedures for reliable and metrically accurate photogrammetric recording. The archaeological literature describes diverse equipment and approaches to photogrammetry. The purpose of this article is to open a discussion about when and how photogrammetry should be employed in arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 29 publications
0
54
0
Order By: Relevance
“…Applications in geomorphology include laboratory flume experiments (Morgan et al, 2017), rockslides and landslides (Niethammer et al, 2012;Russell, 2016), eroding badlands (Smith and Vericat, 2015), fluvial morphology (Javernick et al, 2014;Dietrich, 2015;Bakker and Lane, 2016;Dietrich, 2016a, b), peatland microforms (Mercer and Westbrook, 2016), glacial process dynamics (Piermattei et al, 2016;Immerzeel et al, 2017), river restoration (Marteau et al, 2016), mapping coral reefs (Casella et al, 2016), beach surveying (Brunier et al, 2016), soil erosion (Snapir et al, 2014;Balaguer-Puig et al, 2017;Prosdocimi et al, 2017;Vinci et al, 2017;Heindel et al, 2018), volcanic terrains (James and Robson, 2012;Bretar et al, 2013;Carr et al, 2018), porosity of river bed material (Seitz et al, 2018), grain size estimation of gravel bed rivers (Pearson et al, 2017), and coastal erosion (James and Robson, 2012). In addition, SfM has also been widely used in archaeology for photogrammetric recording of small-scale rock art and artefacts and largescale archaeological sites (Sapirstein, 2016(Sapirstein, , 2018Sapirstein and Murray, 2017;Jalandoni et al, 2018).…”
Section: Structure From Motion (Sfm)mentioning
confidence: 99%
“…Applications in geomorphology include laboratory flume experiments (Morgan et al, 2017), rockslides and landslides (Niethammer et al, 2012;Russell, 2016), eroding badlands (Smith and Vericat, 2015), fluvial morphology (Javernick et al, 2014;Dietrich, 2015;Bakker and Lane, 2016;Dietrich, 2016a, b), peatland microforms (Mercer and Westbrook, 2016), glacial process dynamics (Piermattei et al, 2016;Immerzeel et al, 2017), river restoration (Marteau et al, 2016), mapping coral reefs (Casella et al, 2016), beach surveying (Brunier et al, 2016), soil erosion (Snapir et al, 2014;Balaguer-Puig et al, 2017;Prosdocimi et al, 2017;Vinci et al, 2017;Heindel et al, 2018), volcanic terrains (James and Robson, 2012;Bretar et al, 2013;Carr et al, 2018), porosity of river bed material (Seitz et al, 2018), grain size estimation of gravel bed rivers (Pearson et al, 2017), and coastal erosion (James and Robson, 2012). In addition, SfM has also been widely used in archaeology for photogrammetric recording of small-scale rock art and artefacts and largescale archaeological sites (Sapirstein, 2016(Sapirstein, , 2018Sapirstein and Murray, 2017;Jalandoni et al, 2018).…”
Section: Structure From Motion (Sfm)mentioning
confidence: 99%
“…Additionally, this method was determined to be a more expedient method compared to hand-drawn maps of individual burials, thereby saving on time and financial resources. Other scholars have also found that 3D documentation methods are time efficient and more accurate (Douglass et al 2015;Koenig et al 2017;Novotny 2019;Olson et al 2013;Sapirstein and Murray 2017).…”
Section: Sfm Photogrammetry Of Burials: Design and Objectivesmentioning
confidence: 99%
“…Select features were recorded in more detail using a combination of photogrammetry and topographic survey; aerial photographs were taken by a kite-mounted Olympus TG-4 camera alongside manual photography using the same camera. These 16-megapixel photographs were processed into three-dimensional models, digital elevation models and orthophotographic meshes with high metric accuracy (Sapirstein & Murray 2017). Spatial referencing was provided by ground control points recorded using Emlid Reach RS+ Real-Time-Kinematic Differential GPS units with a fixed base located at the URAP campsite and a rover collecting corrected data with sub-centimetre accuracy from a distance of up to 6km.…”
Section: The Uronarti Regional Archaeological Projectmentioning
confidence: 99%